1983
DOI: 10.1016/0022-3697(83)90144-0
|View full text |Cite
|
Sign up to set email alerts
|

AES/STEM grain boundary analysis of stabilized zirconia ceramics

Abstract: A~~act-Semi~uantitative Auger Electron Spectroscopy (AES) on pure monophasic (Z~*)~.~(YO,.~~,,, was used to determine the chemical composition of the grain boundaries. Grain boundary enrichment with Y was observed with an enrichment factor of about 1.5. The difference in activation energy of the ionic conductivity of the grain boundary compared with the bulk can be explained by the Y segregation.When B&O3 is introduced into this material and second phase appears along the grain boundaries of the cubic main pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 14 publications
10
50
0
Order By: Relevance
“…A ZY17 sample doped with 2.2 mol% Bi203, which contains 20 mol% monocTinic ZrO 2, shows a large depression of the grain boundary semicircle in the complex impedance diagram [8]. This depression is related to inhomogeneous grain boundaries, which are also found by STEM analysis [11]. The conductivity of the Bi20 R rich grain boundary of the ZYB sample, calculated as a specific conductivity is lower than that of stabilized Bi203 Ell.…”
Section: Electrical Measurementsmentioning
confidence: 68%
See 1 more Smart Citation
“…A ZY17 sample doped with 2.2 mol% Bi203, which contains 20 mol% monocTinic ZrO 2, shows a large depression of the grain boundary semicircle in the complex impedance diagram [8]. This depression is related to inhomogeneous grain boundaries, which are also found by STEM analysis [11]. The conductivity of the Bi20 R rich grain boundary of the ZYB sample, calculated as a specific conductivity is lower than that of stabilized Bi203 Ell.…”
Section: Electrical Measurementsmentioning
confidence: 68%
“…In ~o~t cases however a monoclinic ZrO 2 phase appears when Bi203 is introduced into ZrO2-Y20 R. The presence of a monoclinic phase with low conductivity decreases the 6e~hanical stability and causes deterioration of some of the sensor functions [9,10]. In polyphasic materials the cubic phase tends to reach a composition of (Zr02) 0 79(Y01 5)0 21 after completion of the reaction [2,11]. This suggests the occurrence of'an invariant point in the ternary phase diagram close to this composition and consequently the impossibility of preparing a monophasic Bi containing material with the optimal Zr/Y ratio for electrical conductivity (ZY17).…”
Section: Introductionmentioning
confidence: 99%
“…This effect was confirmed later by Miyayama and Yanagida. 10 The first quantitative assessment of segregation in zirconia was reported by Winnubst et al 11 Using AES, they established that segregation in YSZ resulted in enrichment of the surface layer in yttrium. Subsequent quantitative analyses by Burggraaf et al, 12,13 using both AES and XPS, have revealed the following key features:…”
Section: Segregation In Zirconia Equilibrium Segregationmentioning
confidence: 99%
“…The yttrium grain boundary segregation factor in cubic ZrO 2 is around 2 [33,34]. By polishing away the surface segregation layer and then annealing the samples at different temperatures for sufficiently long time, it has been proven that the yttrium segregation profile is almost frozen at temperatures below 1000 C [33,34].…”
Section: Grain Boundary Defect Structurementioning
confidence: 99%